THU0346 EVALUATION OF A NOVEL PARTICLE-BASED ASSAY FOR DETECTION OF MYOSITIS SPECIFIC ANTIBODIES. (June 2019) - Mahler, Michael; Malyavantham, Kishore; Richards, Michaelin; Bentow, Chelsea; Casas, Silvia; Balada, Eva; Sanz, Maite; Angeles Martinez, M.; Selva-O'callaghan, Albert
Abstract : Background: Myositis specific antibodies (MSA) represent important diagnostic tools and also help stratify idiopathic inflammatory myositis (IIM) patients with particular clinical features, treatment responses, and disease outcomes. Standardization of MSA detection is of high importance because these antibodies also have the potential to be used in classification criteria. Objectives: The objective of this study was to evaluate the clinical performance of a novel particle based multi-analyte technology (PMAT) for the detection of MSA as an aid in the diagnosis and also in the differentiation of IIM subtypes. Methods: The study included 464 patient samples collected at Hospital Vall d'Hebron, Autonomous University of Barcelona, most of whom had a diagnosis of IIM (n=264). As controls, samples from patients with myositis like conditions (ML, n=20), rheumatoid arthritis (RA, n=33), systemic lupus erythematosus (SLE, n=40), Sjögren's syndrome (SjS, n=25), infectious diseases (ID, n=40) and healthy individuals (HI, n=42) were included. All samples were tested using a novel fully automated particle-based multi-analyte technology (PMAT, Inova Diagnostics, research use only; Jo-1, PL-7, PL-12, EJ, Mi-2b, NXP2, SAE, TIF1y, MDA5, HMGCR, SRP) which utilizes paramagnetic particles with unique signatures and a digital interpretation system. Results: The sensitivity/specificity of the individual MSA were: 19.7%/100% (Jo-1), 7.2%/100.0% (Mi-2), 3.0%/99.0% (NXP2), 3.8%/100.0% (SAE), 2.7%/100.0% (PL-7), 1.9%/99.5 (PL-12), 1.1%/100.0% (EJ), 15.5%/99.5% (TIF1y), 8.3%/98.5% (MDA5), 6.1%/99.0% (HMGCR) and 1.9%/98.5% (SRP). The overall clinical performance was: sensitivity 68.2% (95% confidence interval 62.3-73.5%), specificity 94.0% (95% CI 89.8-96.5%) and odds ratio 33.8. In the table below, the sensitivity and specificity of each analyte for IIM subtypes was calculated along with odds ratio. Conclusion: The novel PMAT used to detect a spectrum of MSA in IIM on a fully automated system showed good sensitivity and specificity in line with the known associations of MSA. Sensitivities and specificities of the individual MSA are within expected ranges. Lastly, the individual markers help to stratify patients into IIM subtype which is important for management of the patients. Disclosure of Interests: Michael Mahler Employee of: Inova Diagnostics (Not pharmaceutical, diagnostics company), Kishore Malyavantham Employee of: Inova Diagnostics, Michaelin Richards Employee of: Inova Diagnostics, Chelsea Bentow Employee of: INOVA Diagnostics, Silvia Casas Employee of: Inova Diagnostics, Eva Balada: None declared, Maite Sanz: None declared, M. Angeles Martinez: None declared, Albert Selva-O'Callaghan: None declared